Neutrophil count to albumin ratio as a new predictor of mortality in patients with COVID-19 ınfection - Varim,Ceyhun (2020)
SUMMARY BACKGROUND Coronavirus Disease 2019 is an acute inflammatory respiratory disease. It causes many changes in hemogram parameters. Low albumin levels are associated with mortality risk in hospitalized patients. The aim of the present study is to reveal the place of neutrophil count to albumin ratio in predicting mortality in patients with COVID-19. METHODS 144 patients, 65 females and 79 males, were included in the study. Patients were divided into 2 groups. Group 1 was the non-severe group (n:85), and Group 2 was severe (n:59). Demographic data, neutrophil, lymphocyte and platelet counts, albumin and C-reactive protein (CRP) levels were recorded. Neutrophil count to albumin ratio (NAR) was calculated by dividing the absolute neutrophil counts by the albumin levels. The NAR and levels of the two groups were then compared. RESULTS There were no significant differences in gender and platelet count (201 vs. 211 K/mL) between the groups (p>0,05). Ages (62.0 ± 14.3 vs 68.6 ± 12.2 years), albumin (33.1 vs 29.9 gr/L), CRP (33 vs 113 mg/l), neutrophil count (4 vs 7.24 K/mL), WBC counts (6.70 vs 8.50 K/mL), NAR values (113.5 vs 267.2) and number of Death (5 vs 33) were found to be statistically higher (p <0.001) in Group 2 than in Group 1. The NAR value of 201.5 showed mortality in all patients with COVID-19 to have 71.1% sensitivity and 71.7% specificity (AUC:0.736, 95% CI: 0.641-0.832, p<0.001) CONCLUSION The present study showed that NAR levels can be a cheap and simple marker for predicting mortality in patients with COVID-19.